2019
DOI: 10.1111/bph.14836
|View full text |Cite
|
Sign up to set email alerts
|

Non‐coding RNAs in bone remodelling and bone metastasis: Mechanisms of action and translational relevance

Abstract: Bone metastases are frequent complications in patients with advanced cancer, which can be fatal or may rapidly impede the quality of life of patients. Current treatments for patients with bone metastases are palliative. Therefore, a better understanding of the molecular mechanisms that precede the overt development of skeletal lesions could lead to better therapeutic interventions. In this review, we present evidence that non-coding RNAs (ncRNAs) such as long non-coding RNAs (lncRNAs), microRNAs (miRNAs), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 150 publications
(365 reference statements)
0
30
0
Order By: Relevance
“…Several microRNAs and long non-coding RNAs have been reported as differentially expressed during osteogenesis (Ell and Kang, 2014;Huynh et al, 2017;Xie et al, 2017;Puppo et al, 2019). Their involvement in bone cancer and metastasis is well addressed (Puppo et al, 2019). Nevertheless, little is known about the regulation of the expression and the role of circRNAs in bone development and in bone pathologies.…”
Section: Circrnas In Osteogenic Differentiationmentioning
confidence: 99%
“…Several microRNAs and long non-coding RNAs have been reported as differentially expressed during osteogenesis (Ell and Kang, 2014;Huynh et al, 2017;Xie et al, 2017;Puppo et al, 2019). Their involvement in bone cancer and metastasis is well addressed (Puppo et al, 2019). Nevertheless, little is known about the regulation of the expression and the role of circRNAs in bone development and in bone pathologies.…”
Section: Circrnas In Osteogenic Differentiationmentioning
confidence: 99%
“…The expression of oncomiRs or oncosuppressor miRNAs is often time related, and they regulate and promote different steps of tumour progression from early to advanced stages. In bone metastasis, several miRNAs have been reported to act as drivers of the molecular changes within cells [16]. The expression of some miRNAs has been associated with an invasive and aggressive phenotype of cancer cells that promote their dissemination, or with their preference to metastasise in bone.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that CircRNAs may participate in the pathological process of a variety of orthopedic diseases, such as osteoarthritis, osteoporosis, and so on [7]. They can promote the proliferation of osteoblasts and the coupling process of osteogenesis and angiogenesis to treat fracture and osteoporosis [8][9]. Therefore, CircRNAs may become a biomarker for diagnosis and prognosis and a potential therapeutic target in orthopedics.…”
Section: Introductionmentioning
confidence: 99%